Fighting colonialism with hegemonic culture : native American appropriation of Indian stereotypes - Schwarz, Maureen Trudelle, 1952- (State University of New York Press, 2013)
"Explores how American Indian businesses and organizations are taking on images that were designed to oppress them. How and why do American Indians appropriate images of Indians for their own purposes? How do these representatives promote and sometimes challenge sovereignty for Indigenous people locally and nationally? American Indians have recently taken on a new relationship with the hegemonic culture designed to oppress them. Rather than protesting it, they are earmarking images from it and using them for their own ends. This provocative book adds an interesting twist and nuance to our understanding of the five-hundred year interchange between American Indians and others. A host of examples of how American Indians use the so-called "White Man's Indian" reveal the key images and issues selected most frequently by the representatives of Native organizations or Native-owned businesses in the late twentieth and early twenty-first centuries to appropriate Indianness."--Publisher's website